Factors affecting the quality of QPF: a multi‐method verification of multi‐configuration BOLAM reforecasts against MAP D‐PHASE observations. (10th June 2013) - Casaioli, Marco; Mariani, Stefano; Malguzzi, Piero; Speranza, Antonio
ABSTRACT This paper discusses the results of a quantitative precipitation forecast (QPF) verification study aimed at comparing different alternative new configurations of the meteorological BOlogna Limited Area Model (BOLAM) to be implemented in 2013 into the ISPRA's Hydro‐Meteo‐Marine forecasting system (SIMM) in place of the currently operational version, dated 2009. Five new configurations are defined after considering several combinations of the following model settings: horizontal grid spacing, domain extension, initial and boundary conditions, nesting design and the BOLAM code version. Such testing configurations are inter‐compared with the operational BOLAM version following a multi‐method approach including Fourier spectral analysis, several categorical scores, quasi‐relative operating characteristic diagram and visual inspection of the spatial distributions of the contingency table elements. Rain gauge measurements available between June and November 2007 within the international initiative 'Demonstration of Probabilistic Hydrological and Atmospheric Simulation of flood Events in the Alpine region' of the Mesoscale Alpine Programme (MAP D‐PHASE) are considered as observational dataset. A 6 month reforecast campaign is performed in order to produce, for each compared configuration, the corresponding forecast series. Results show that decreasing model grid spacing and simultaneously increasing model domain extension is effective in improving the QPF quality when higher‐resolution initial and boundary conditions are directly applied to BOLAM, without using a coarser‐resolution parent model run. Therefore, such skilful configuration has been deployed in late 2012 within the international research programme 'HYdrological cycle in Mediterranean EXperiment' (HyMeX). On the contrary, when keeping the low‐resolution, double nesting configuration, improving input data decreases the QPF performance. Copyright © 2013 Royal Meteorological Society